2020
DOI: 10.12973/eu-jer.9.3.1127
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students’ Challenging Learning Experiences and their Changing Attitude towards Academic Performance

Abstract: This study determined the challenging learning experiences of engineering students while completing their degree program as factor that might influence to their changing attitude towards achieving higher academic performance. Mixed method of research was utilised in the study considering the total population of 75 graduating students for quantitative and 12 students for qualitative part of the study using focus group discussion. Results showed that engineering students have significantly higher level of positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Learning experience, including learners' beliefs and experiences about the learning context, is a clear indicator of students' academic performance and affects their sense of belonging [23]. Therefore, understanding the key factors affecting students' sense of belonging, their learning experience, as well as how these factors are linked is necessary to develop students' positive sense of belonging.…”
Section: Antecedents Of Sense Of Belonging In Learningmentioning
confidence: 99%
“…Learning experience, including learners' beliefs and experiences about the learning context, is a clear indicator of students' academic performance and affects their sense of belonging [23]. Therefore, understanding the key factors affecting students' sense of belonging, their learning experience, as well as how these factors are linked is necessary to develop students' positive sense of belonging.…”
Section: Antecedents Of Sense Of Belonging In Learningmentioning
confidence: 99%
“…The researchers concluded that Tanzanian students had positive attitudes towards mathematics, and the reasons for these attitudes were: (1) feeling joy when learning mathematics, (2) academic competence of the student, (3) teaching methods, (4) classroom educational environment, (5) availability of scientific means in the school, and (6) tests results. Several studies indicate the influence of other factors such as colleagues and friends (He, 2007;Yang, 2013), family and parents (Davadas & Lay, 2020), school (Laguador & Dotong, 2020;Yang, 2013), teachers' personal characteristics (Al Shabibi, Al Mantheri, & Al Rashdi, 2019;Blazar & Kraft, 2017;Sakiz, Pape, & Hoy, 2012), teachers' knowledge of content (Simmers, 2011), language (Mazana, Montero, & Casmir, 2019), and how mathematics relates to daily life (Yılmaz, Altun, & Olkun, 2010).…”
Section: Reasons For Students' Attitudes Toward Mathematicsmentioning
confidence: 99%